2014
DOI: 10.1637/10733-112513-reg.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Capillary and Myofiber Density in the Pectoralis Major Muscles of Rapidly Growing, High-Yield Broiler Chickens During Increased Heat Stress

Abstract: Skeletal muscle development proceeds from early embryogenesis through marketing age in broiler chickens. While myofiber formation is essentially complete at hatching, myofiber hypertrophy can increase after hatch by assimilation of satellite cell nuclei into myofibers. As the diameter of the myofibers increases, capillary density peripheral to the myofiber is marginalized, limiting oxygen supply and subsequent diffusion into the myofiber, inducing microischemia. The superficial and deep pectoralis muscles cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 23 publications
1
44
0
1
Order By: Relevance
“…The total vessel number decreased with age in unaffected broiler chickens (Fig. 2), which is consistent with previous findings (Joiner et al, 2014;Radaelli et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The total vessel number decreased with age in unaffected broiler chickens (Fig. 2), which is consistent with previous findings (Joiner et al, 2014;Radaelli et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…In addition to the higher initial myofibre diameter compared with layers, the myofibre diameter increases with age in high-yielding broilers, while the total vessel density decreases (Joiner et al, 2014;Radaelli et al, 2017). Capillaries, rather than other vessels, appear to increase in number in response to the myofibre hypertrophy in order to maintain the necessary blood supply to growing muscle (Joiner et al, 2014;Radaelli et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, on day 60, when the birds became very large, they were not able to liberate heat quickly enough, even though the house temperature was only 14.4°C–16.7°C (58.0°F–62.1°F). An earlier study has reported that the relative number of capillaries and blood vessels per unit of body surface area becomes lower with rapid myofiber growth in breast muscle ( Joiner et al., 2014 ), which may compromise the cooling capability of large birds. An insufficient cooling capability in big birds is a common problem in modern broiler production.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated pCO 2 in conjunction with a decline in pH in WB affected birds is possibly indicative of an acid-base disorder called respiratory acidosis. While respiratory acidosis is classically defined in terms of arterial blood gas measurements, the high correlation of arterial and venous pCO 2 and pH is wellestablished in humans, dogs, and chickens, as is the use of venous measurements for investigation of acid-base disturbances (Forster et al, 1972;Ilkiw et al, 1991;Wideman et al, 2003;Yildizdaş et al, 2004). Respiratory acidosis occurs when the body produces more CO 2 than can be removed by the lungs (D'Addesio, 1992).…”
Section: Blood Analysismentioning
confidence: 99%
“…Impaired venous return from phlebitis may exacerbate what some characterize as existing vascular insufficiency in the pectoralis major of commercial broilers. At the cellular level, large breast muscles are produced by increasing the number, diameter, and length of muscle fibers (Scheuermann et al, 2004;Roy et al, 2006), causing a reduction of capillary density among other effects (Hoving-Bolink et al, 2000;Joiner et al, 2014).…”
Section: Wbmentioning
confidence: 99%